HUKUM DEEPFAKE MENURUT ISLAM: KAJIAN FIKIH KONTEMPORER - Nabila Aulia Rahmah; Siti Zubaidah; Mahlil Nurul Ihsan (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2026)
The rapid development of digital technology, particularly deepfake technology based on Generative Adversarial Networks (GANs) capable of producing highly realistic synthetic visual content, has raised significant legal and ethical questions within the Islamic scholarly tradition. This study aims to analyze the legal status of deepfake technology according to Islamic jurisprudence and provide normative guidance for the Muslim community in responsibly addressing the challenges of the digital age. Using a library research method with a normative-analytical approach, this study is grounded in verses of the Qur’an, hadith, and the framework of maqasid al-shar’iyah to categorize the use of deepfakes. The findings indicate that the use of deepfakes involving deception (tadlis), the deliberate spread of falsehoods (ifk), and distortion of meaning (tahrif al-ma’na) is deemed haram because it violates the principles of sidq (truthfulness) and amanah (trustworthiness), and causes widespread social harm (mafsadah ‘ammah). Conversely, the transparent and non-deceptive use of deepfakes, specifically for genuine educational purposes, can be justified based on the principle of maslaḥah mursalah. This study proposes the concept of fiqh al-asalah al-raqamiyyah (digital authenticity jurisprudence) as a contemporary normative framework for evaluating artificial intelligence based on Islamic values.